Sequence stratigraphy and facies architecture of a mound‐shoal‐dominated dolomite reservoir in the late Ediacaran Dengying Formation, central Sichuan Basin, SW China. (27th June 2018) - Hu, Mingyi; Gao, Da; Wei, Guoqi; Yang, Wei; Xie, Wuren
Abstract : The late Ediacaran Dengying Formation is one of the oldest carbonate microbial mound and shoal reservoirs in the world. This formation has recently attained widespread attention with the significant discovery of a huge volume of natural gas in the central part of the Sichuan Basin, South China. To fully understand the depositional processes and impacts on the reservoir, a comprehensive study of the sequence stratigraphy and facies architecture as well as reservoir analysis was undertaken by integrating analysis of seismic, well‐logging, and core data. The D4 member consists of nine types of lithofacies representing distinguished depositional environments. These types of lithofacies can be grouped into five types of lithofacies associations, which are platform‐margin shoal, mound‐shoal complex, microbial mound, lagoon, and tidal flat. The platform margin was dominated by shoal and mound‐shoal complexes, whereas the platform interior contained microbial mounds, lagoon, and tidal flat facies. We constructed a high‐frequency sequence stratigraphy framework and identified two third‐order sequences (SQ1 and SQ2) in the Dengying Formation and five fourth‐order sequences (SQ2‐1 to SQ2‐5) in the fourth member of the Dengying Formation (the D4 member). In the D4 member, the thickness of the mound‐shoal complex increases from the bottom to the top. The reservoir spaces in this Formation generally have low porosity and low permeability and include dissolution vugs and caves, and intercrystalline vugs and pores. Three types of reservoirs are identified, which are early‐stage karst mound‐shoal reservoirs, late‐stage karst superimposed reservoirs, and other factors impacted reservoirs. Microbial mound and shoal facies are the material basis for a favourable reservoir, with the key factor for the improvement of reservoir quality being early‐stage meteoric‐water dissolution related to fourth‐order sequence boundaries. The tectonic unconformity that was formed at the end of the Sinian Stage dominates the development and distribution of the most beneficial reservoir beds. Organic acid, hydrothermal fluid, and tectonic fracturing processes modified the reservoir beds in advance. Results from our investigation enable us to propose a model for the depositional evolution and reservoir formation in the D4 member of the Dengying Formation.